Design of Tuneable CMOS Up-Conversion Mixer for RF Integrated Circuit. - Ramiah, Harikrishnan; Azni Zulkifli, Tun Zainal (2004)

(untitled)
A high Frequency 1-3GHz tuneable pure NMOS Up-conversion mixer topology is presented. The mixer is implemented in a 0.25μm CMOS process technology.